The Role Of Zakat In The Digital Era 4.0 For Families In Solving Social Problems Integrated With Technology - Asman, Asman (Universitas Islam Negeri Raden Intan Lampung, 2023)
Management in the management of zakat nationally was socialized after the issuance of Law Number 38 of 1999 concerning Zakat Management in Indonesia. However, in the course of the management of zakat management in Indonesia, there are problems in the formation of zakat management at the regional, district, sub-district and zakat managers in the form of community organizations. So that in zakat management the distribution of zakat is not right on target so that zakat management gets pros and cons in the community. The purpose of this study is to examine more deeply the implications of zakat management in Indonesia through the literature so that answers are obtained such as the contribution of solutions in this study. The methodology in this research is the type in this research is a qualitative research literature. While the approach in this study uses a normative juridical approach. The results in this study are the management of zakat management must be adjusted to the needs of those who are entitled to receive it according to the socio-economic conditions of Muslim citizens.Keywords: Role, Zakat, digital era 4.0, family, technology